PREVALENSI KASUS DEMAM BERDARAH DENGUE DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR PERIODE JUNIâ€NOVEMBER 2014 - Arvinth Ganesan (Intisari Sains Medis, 2015)
Dengue fever, also known as breakbone fever, is a mosquitoâ€borne infection that causes a severe fluâ€like illness. Dengue can vary from mild to severe; the more severe forms include dengue shock syndrome and dengue haemorrhagic fever (DHF).The main purpose of this research is to investigate and analyse the prevalence of dengue cases that has been reported in Rumah Sakit Umum Pusat Sanglah, Denpasar from the month of June to November in the year of 2014. The design research used for this study is Descriptive studyof cohort retrospective. The target population is basically the population of patients in Rumah Sakit Umum Pusat Sanglah, Denpasar, who has been diagnosed with dengue fever. This research is carried out using medical data of 429 patients. Total of 118 cases are reported as outpatients and 311 cases are inpatient. Based on the research, the highest percentage of case reported is in the month of June with 28.20% of total cases. The percentage is then followed by 22.14% in July, 15.62 in August, 11.89% in September, 11.42% inOctober, and only 10.73% in November. Conclude can be made that prevalence of dengue fever which has been reported in RSUP Sanglah from the month of June to November 2014 has been decreasing step by step. It is hoped this study will be useful for the control of dengue cases in the future.